A two pan feeding trial with companion dogs: considerations for future testing - Vondran, Jodi C. (Kansas State University, 2013)
Palatability of pet foods is judged by the use of animals in colonies. Pet food manufacturers would like to understand how palatable a food is compared to another food. This generally is accomplished by a two pan test where a pet has the opportunity to freely choose between two foods. Preference is evaluated through the use of an intake ratio, the ratio of the amount of test food consumed divided by the total amount of the foods consumed. Although this is easy to do in laboratories, another option would be to do such studies with animals in more ‘real-life’ home environments. The purpose of this study was to develop, and test a method to capture feeding information from a study of canines in the home environment and analyze the results of the palatability tests. Individual dog owners were screened for information on the household and pets. Twenty-five dogs of different ages, breeds and sizes were selected to participate on the in-home panel. Seven different palatability tests were performed using the in-home panel with four of those tests being replicated; a total of 11 comparative tests. These dogs were tested using a proprietary computer-based technology that collected information about intake of each food for each individual dog for a duration of seven days for each of the 11 comparative studies. Data was analyzed and resulted in showing that differences between foods can be found. Statistical analyses compared initial day one data to subsequent day data collected during each study to determine whether a full seven day test was needed. In addition, comparisons were made to compare the impact of prior foods eaten to subsequent preferences of the dogs. Results of the in-home panel were the same on day one as for all seven days of testing. Also, previous exposure to a food did not alter subsequent preference for that food. Such data has implications for pet food manufacturers related to timing and cost of testing.
Keywords: Palatability; Companion Animals; Dog; Home Setting; Animal Behavior; Sensory; Animal Sciences (0475); Behavioral Sciences (0602)